COVID-19 Pandemic Affects Children's Education but Opens up a New Learning System in a Romanian Rural Area - Oana Miruna Oprea; Iuliana Elena Bujor; Alexandra Elena Cristofor; Alexandra Ursache; Bianca Sandu; Ludmila Lozneanu; Cristina Elena Mandici; Andreea Silvana Szalontay; Marcel Alexandru Gaina; Daniela-Roxana Matasariu (MDPI AG, 2023)
(1) Background: In the context of the COVID-19 pandemic, the educational system in Romania faced major challenges. Online knowledge development was necessary and mandatory during this time; (2) Methods: our study included a group of 140 preadolescents and used a phenomenology qualitative method to investigate if the novel online teaching, implemented in a hurry during the pandemic without any previous teacher training, managed to replace face-to-face teaching; (3) Results: The students have expressed their joy for online courses, as long as they are kept interactive. Even though they feel nervous and worried when it comes to evaluation, the students claim they feel capable to learn all of the learning materials. Most of them are pleased by classes and do not get bored during them, feeling constantly motivated to actively participate in dialogue; (4) Discussions: Despite the lack of teaching-method standardization, our learning providers succeeded in accomplishing their tasks during online courses. Even in remote rural areas, they managed to assure the means for these children to access and take part in online courses; (5) Conclusions: our learning system must offer teachers the possibility to emphasize online education using adequate training programs aiming to develop technical and online pedagogical skills.